Adverse childhood experiences and subsequent experiences of intimate partner violence in adulthood: a gender perspective - Zheng Tian; Nan Zhang; Yimiao Li; Yibo Wu; Lan Wang (Epidemiology and Psychiatric Sciences)
Abstract Aims Investigate the prevalence of adverse childhood experience (ACE) and intimate partner violence (IPV) using a large representative Chinese sample, explore the association mechanism between ACE and adult exposure to IPV and to examine gender differences.